Low copy number of FCGR3B is associated with lupus nephritis in a Chinese population - Zheng, Zhaohui (Exp Ther Med, 2017)
Lupus nephritis (LN) is a polygenic disease caused by an interaction between hereditary and environmental factors. Numerous gene copy number variations have been identified to contribute to this disease. Previously, immunoglobulin (Ig)G Fcγ receptor 3B (FCGR3B) copy number variation (CNV) was reported to be associated with LN in the Caucasian population. However, the effect of FCGR3B CNV on LN in the Chinese population remains unknown. The present study aimed to investigate whether CNVs of FCGR3B are associated with LN in the Henan Chinese population. FCGR3B CNVs were determined in 142 LN patients and 328 healthy controls. A modified methodology based on competitive polymerase chain reaction, a Multiplex AccuCopy™ kit was used to detect FCGR3B copy number. Clinical and laboratory data was collected retrospectively from medical records. To evaluate associations between FCGR3B CNVs and LN susceptibility, the present study calculated the odds ratios using a logistic regression analysis. The current study identified that the distribution of FCGR3B copy number was significantly different between LN and healthy controls (P=0.031). A low copy number (<2) of FCGR3B was significantly enriched in LN patients (P=0.042), and was a risk factor for LN (odds ratio=2.059; 95% confidence interval, 1.081–3.921; P=0.028). However, a high copy number (>2) had no effect on LN. There were no associations between FCGR3B CNV and clinical phenotypes of LN. The results from the present study demonstrate that a low copy number of FCGR3B is a risk factor for LN in a Chinese population.